THE IMPACT OF STRATEGIC ENTREPRENEURSHIP ORIENTATION IN ENHANCING BUSINESS COMPETITIVENESS - liqaa Mutter Atti; Adnan Saad Tuama Al-Sukaini (American Journals, 2023)
The research aims to identify the extent of the impact of the strategic entrepreneurship orientation on business competitiveness, and to reveal the extent to which the organization under discussion is able to employ the dimensions of the strategic entrepreneurship orientation in enabling it to be a key player in competing with its counterparts in the local and regional market. The company in question adopts strategic entrepreneurship to adapt to the changes taking place in the external environment, especially competitors, after the trend to the open market became for the private sector to take the lead in a market that is diversified in products and increased competition. The researcher used a questionnaire prepared for this purpose, consisting of two variables; the first is the independent variable, strategic entrepreneurship in its three dimensions (creativity, risk, initiative), Business competitiveness came as a dependent variable with dimensions (quality, flexibility, delivery) for a sample of (100) person and using the statistical package (spss v.22). In analyzing the data, the study reached the most important conclusion, which is the research sample company's lack of two dimensions (creativity and risk) as basic foundations in strategic leadership, which made it lose the possibility of obtaining competitive priorities characterized by flexibility and the ability to adapt to environmental developments.